2020
DOI: 10.7150/jca.46563
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Nomogram for Early Death of Metastatic Gastric Cancer: A Retrospective Study in the SEER Database and China

Abstract: Background: To identify associated risk factors and develop a predictive nomogram for the early death of metastatic gastric cancer patients. Methods: A total of 4575 patients in the SEER cohort and 220 patients in the Chinese cohort diagnosed with metastatic gastric cancer in our Cancer Center were obtained. Univariate and multivariate logistic regression models were used to identify independent risk variables for early death. A predictive nomogram and a web-based probability calculator were developed and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Thus, precise forecasts of the survival rates of LMS patients with lung metastasis is essential if clinicians are to make effective medical decisions. The nomogram is a visualization tool for oncology-related prediction that can help clinicians to make individualized survival predictions and offer personalized treatments (21,22). However, previously, no nomogram for predicting OS and CSS in LMS patients with lung metastasis existed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, precise forecasts of the survival rates of LMS patients with lung metastasis is essential if clinicians are to make effective medical decisions. The nomogram is a visualization tool for oncology-related prediction that can help clinicians to make individualized survival predictions and offer personalized treatments (21,22). However, previously, no nomogram for predicting OS and CSS in LMS patients with lung metastasis existed.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 For malignant and advanced tumors, only a few studies have investigated early death. 9 11 Based on different diseases and risk factors, many studies have defined early death. 27 29 Using a definition of early death that is too long or short is not conducive for clinicians to provide effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on high-risk factors have been conducted in gastrointestinal tumors and endometrial cancers, but few have been reported in LUAD. 9 11 Furthermore, risk factors for early death in patients with bone metastasis of LUAD have not been well documented. Therefore, analyzing risk factors of early death (survival time ≤7 months) in patients with LUAD and bone metastasis is clinically significant.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the flow diagram of the patient selection criteria. Considering the malignancy of pancreatic cancer and definition of previous studies, early death was defined as death within 3 months after first diagnosis ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%